2006
DOI: 10.1161/circulationaha.105.000521
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Myoblast Transplantation in Ischemic Heart Failure

Abstract: Background-Skeletal myoblast (SM) transplantation (Tx) in a post-myocardial infarction (MI) scar experimentally improves left ventricular (LV) ejection fraction (EF). Short-term follow-up (FU) studies have suggested that a similar benefit could clinically occur despite an increased risk of LV arrhythmias. Methods and Results-We report the long-term FU of the first worldwide cohort of grafted patients (n ϭ9, 61.8Ϯ11.6 years, previous MI, EF Յ35%) operated on (autologous SM Tx and bypass surgery) in 2000 to 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
147
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 19 publications
2
147
1
5
Order By: Relevance
“…[41][42][43][44][45][46][47] The first phase II, multicentre, double-blind, placebo-controlled, doseranging, randomised study using myoblast transplantation as an adjunct to CABG, the MAGIC trial, was recently stopped because of lack of efficacy. Preliminary results from this trial suggest a modest increase in ejection fraction, as assessed by nuclear imaging and a reduction in left ventricular volumes.…”
Section: Cell Transplantation In Clinical Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43][44][45][46][47] The first phase II, multicentre, double-blind, placebo-controlled, doseranging, randomised study using myoblast transplantation as an adjunct to CABG, the MAGIC trial, was recently stopped because of lack of efficacy. Preliminary results from this trial suggest a modest increase in ejection fraction, as assessed by nuclear imaging and a reduction in left ventricular volumes.…”
Section: Cell Transplantation In Clinical Researchmentioning
confidence: 99%
“…48 The final results of this trial have not yet been reported. Four of the phase I studies involved myoblast transplantation as an adjunct to CABG, 41,42,44,45 one involved endoventricular injections of myoblasts 46 and one study used a coronary sinus approach. 47 Generally, patients had signs of congestive heart failure class 2-3 (NYHA), with two-to three-vessel coronary disease and an ejection fraction ranging between 20 and 40%.…”
Section: Cell Transplantation In Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers tried to force myocytes to divide using molecular maneuvers, 7,8 force neonatal myocytes to engraft into mature hearts, 9 and even force chimeric marriage between skeletal muscle and the heart in attempts to restore contractile function. 10,11 A lot of hearts were broken, but we were not doing a very good job of fixing them.…”
mentioning
confidence: 99%
“…Both in vitro studies [7] and human trials [8] have shown the propensity of SKMBs to induce arrhythmias while exerting mechanical benefit. Further, preliminary in vivo studies in animals and humans have shown that MSCs also can be mechanically beneficial [9][10][11].…”
mentioning
confidence: 99%